EFEKTIVITAS MEDIA POWER POINT INTERAKTIF TERHADAP HOTS PADA ERA SOCIETY 5.0 DI SEKOLAH DASAR - Rahmi Yulia; Desyandri (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2022)
This study aims to test the effectiveness of interactive powerpoint media on higher order thingking skills in learning in the era of society 5.0. This research is a quasy experiment design. The design form of this study is Nonequivalent Control Group Design. The population in this study was all class V students of SDN 11 Pudung which amounted to 56 people. The sampling technique in this study used purposive sampling technique. The sample was 28 VA class learners as an experimental class and 28 VB class learners as a control class. The type of instrument that will be used in this study is in the form of an essay test of 5 questions. Hypothesis testing in this study used t-test assisted application program SPSS 20.0 for Windows. The results showed that interactive powerpoint media applied in experimental classes were very effective against higher order thingking skills. The hypothesis test results with a sig value of 0.003 smaller than the significance level of 0.05 can then be made a decision that H0 is rejected and H1 is accepted where there is a significant difference between the higher order thingking skill of the control class and the experimental class.